Minimum energy path problem for peptide folding dynamics - Cruz, Marnoel A.; Villar, John Justine S. (Quezon City College of Engineering, University of the Philippines Diliman, 2019)
Predicting the three-dimensional structure of the protein from its sequence involves a complete understanding of the forces driving the protein to fold. Each possible conformation of the protein yields a corresponding potential energy, which defines its stability. The relationship between the potential energy of a conformation to its geometry is usually referred to as a potential energy surface (PES). Determining a path between relative minima can greatly assist in determining the factors affecting protein folding, which is why it would be a great progress to determine how peptide folding dynamics work. This paper aims to determine the minimum energy path between two minima given the coordinates and corresponding energies of all minima of a potential energy surface (PES). Three of the 20 log files containing phi, psi, and the energy values was used in order to represent the PES of the three amino acids chosen using a 25 x 25 grid. Saddle points are then identified by partitioning the input grid into horizontal and vertical slices and determining if its a maximum on the horizontal slice and a minimum on the vertical slice , or vice versa. The Bellman-Ford algorithm was used to generate the paths in the images. Adjusting the problem to finding all-pairs shortest paths will result in using other common path finding algorithms such as Floyd-Warshalls algorithm, among others. Along the phi, psi, and energy values, the log files also served as the source of the coordinates for the 3D visualization of the molecule as it traverses the path.
Thesis (Bachelor of Science in Computer Science)--University of the Philippines Diliman
Keywords: Protein folding -- Mathematical models